Algae-Based Biorefinery as a Sustainable Renewable Resource - Salami, Robab (Circ Econ Sustain, 2021)
Algae are a large and diverse group of autotrophic organisms that are multicellular and single-celled and found in a variety of environments. Biofuel production and value-added chemicals produced through a sustainable process are represented by the biorefinery of algae. Algae are important because of the production of polysaccharides, lipids, pigments, proteins, and other compounds for pharmaceutical and nutritional applications. They can also be used as raw materials for biofuel production. Moreover, they are useful for wastewater treatment. All these factors have absorbed the attentions of researchers around the world. This review focuses specifically on the potentials, properties, and applications of algae as a sustainable renewable resource, which can be a good alternative to other sources due to their high biomass production, less land required for cultivation, and the production of valuable metabolites.